2013
DOI: 10.1080/10632913.2013.826050
|View full text |Cite
|
Sign up to set email alerts
|

Arts Integration and the Success of Disadvantaged Students: A Research Evaluation

Abstract: Does arts integration contribute to student success for disadvantaged student populations? The introduction to this article compares students' academic performance and arts education in countries outperforming the United States on the recent Trends in International Mathematics and Science Study (TIMSS) and Progress in International Reading Literacy Study (PIRLS) and makes the argument for using arts integration as a way to teach the Common Core standards and align instruction to the Universal Design for Learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 35 publications
2
39
0
2
Order By: Relevance
“…These meta‐analyses produced mixed results. In one review only two of the 18 studies with a strong or moderate causal design reported positive effects (Robinson, ). Many of the studies rated as having strong causal design were small‐scale, had no random allocation and no control groups.…”
Section: Resultsmentioning
confidence: 99%
“…These meta‐analyses produced mixed results. In one review only two of the 18 studies with a strong or moderate causal design reported positive effects (Robinson, ). Many of the studies rated as having strong causal design were small‐scale, had no random allocation and no control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Future research should also address how arts integration impacts students in poverty. One meta-analysis found that specifically integrating dramatic arts conferred positive results on disadvantaged students' grades, social skills and creative thinking (Robinson, 2013). Many interventions are designed to close the achievement gap that exists between learners, and perhaps more AI interventions could also serve this purpose.…”
Section: Future Directionsmentioning
confidence: 99%
“…She reported positive impact on creativity despite having no comparison group. Robinson's (2013) review of different arts integration reported that arts integration (apart from music integration) showed potential of positive effects on academic and other cognitive outcomes as well as social skills. However, it is worth noting that Robinson also writes and develops programme in arts integration.…”
Section: Arts Educationmentioning
confidence: 99%